2017
DOI: 10.21608/jpp.2017.40552
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Heterosis, Combining Ability and Correlation for Yield and its Components in Bread Wheat

Abstract: In order to realize the heterosis, general and specific combining ability of wheat, 28 crosses were synthesised in a 8 × 8 by using half diallel mating system, without reciprocals. Analysis of heterosis over mid parents (MP) as well as better parents (BP) and combining ability were conducted for yield and its contributing traits. The experiment was conducted in 2011-2012 and 2012-2013 seasons at the Experimental Farm of Faculty of Agriculture, Sohag University, Egypt. Heterosis was estimated for grain yield pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…Out of 32, 11 hybrids registered significant and positive heterosis over standard check (Table 3). Similar findings were also reported by earlier worker Motawea (2017).…”
Section: Resultssupporting
confidence: 93%
“…Out of 32, 11 hybrids registered significant and positive heterosis over standard check (Table 3). Similar findings were also reported by earlier worker Motawea (2017).…”
Section: Resultssupporting
confidence: 93%
“…Such result indicates that inheritance of these traits was mainly controlled by non-additive gene effects under such conditions of nitrogen fertilization. These results are supported findings of (Motawea 2017;Farooq et al 2019;Kutlu and Sirel 2019). Mean squares for interactions of either GCA or SCA with nitrogen levels were highly significant for the all studied characters except of GCA x N levels for grain yield/plant, revealing the existence of sensitivity of both types of gene action to variation in nitrogen treatments.…”
Section: Estimates Of Combining Abilitysupporting
confidence: 90%
“…These estimates can then be used to draw conclusions about the genetic systems controlling grain yield and the other important characters as well as the best breeding strategy to be used to improve them. Several researchers found that the additive gene action was important in the inheritance of grain yield (Motawea 2017), plant height (Nathan and Moubarak 2016) and number of spikes/plant (Kamaluddin et al 2007). On the other hand, other investigators mentioned that the non-additive genetic effects played the important role in the inheritance of grain yield (Farooq et al 2019;El-Said 2018;Ayoob 2020) and spike length (El-Hosary et al 2012; Kutlu and Sirel 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the main structural elements of yield -spike length and in most cases thousand kernels weight are controlled by additive gene ef fects. Preponderance of additive gene effects in inheritance of plant height has been reported by a number of other researchers (Yao et al, 2011;Motawea, 2017;Ali et al, 2018;Hassan et al, 2018;Rajput, Kandalkar, 2018;Singh et al, 2018;Talha et al, 2018;Sharma et al, 2019;Ayoob, 2020); for spike length (Kandil et al, 2016;Motawea, 2017;Parveen et al, 2018;Rajput, Kandalkar, 2018;Sadeghzadeh-Ahari et al, 2018;Singh et al, 2018;Farooq et al, 2019;Sharma et al, 2019;Khaled et al, 2020;Shamsabadi et al, 2020); for thousand kernels weight (Hannachi et al, 2017;Motawea, 2017;Ali et al, 2018;Hassan et al, 2018;Ali, 2019;Amin, Towfiq, 2019;Farooq et al, 2019;Khokhar et al, 2019;Sharma et al, 2019).…”
mentioning
confidence: 71%
“…ГЕНЕТИКА РАСТЕНИЙ / PLANT GENETICS et al, 2020); for thousand kernels weight (Topal et al, 2004;Akinci, 2009;Desale, Mehta, 2013;Brahim, Mohamed, 2014;Motawea, 2017;Ali et al, 2018;Hassan et al, 2018;Ali, 2019;Khokhar et al, 2019;Sharma et al, 2019).…”
mentioning
confidence: 99%